TANTANGAN DAN UPAYA PEMERINTAH INDONESIA DALAM MELINDUNGI MASYARAKAT STUDI KASUS: KEJAHATAN SIBER - imam Budiman (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Technological advances in the era of globalization are now unavoidable. All countries in the world are competing in developing technology to facilitate human life. This technological advancement is inseparable from the threats that lurk in every activity. Of course, the role of the state as an actor must protect its citizens from every threat, including technological threats. This makes cyber security required by all countries, including Indonesia. With various challenges faced, as well as several policies implemented, Indonesia is still a country that is vulnerable to attacks in cyberspace. By using a qualitative research method that focuses on describing phenomena through the literature read, this study concludes that optimizing the role of national cyber defense policy can overcome problems that arise due to the advancement of technology in the present time